Good governance and integration for sustainable municipal solid waste management: a case study of Egypt - El Masry, Randa (AUC Knowledge Fountain, 2019)
The management of solid waste has become a major cause of concern over the past few years in both developed and developing countries. For the sustainable development of any nation, proper management of solid waste is very essential. The effect of waste accumulation can be extremely serious for many communities in developing countries. In Egypt, the issue gets more complicated as the municipal solid waste management system lacks good governance and integration among stakeholders due to unclear law and undefined roles among stakeholders. These aspects impose severe health and environmental threats on Egyptian communities and waste its resources. To solve the MSWM issue in Egypt there are several factors to be considered. At first, good governance must take place in terms of equity and inclusiveness among stakeholders especially the informal sector. Besides, rule of law execution is important as to have clear laws and institutional frameworks that are soundly implemented. Also, laws promoting Extended Producer Responsibility (EPR) have to take place. The EPR shifts responsibility from the government and user to producer to organize and finance the collection system for used products. This will lessen the environmental stress and also benefits the producer and user. Moreover, promoting source reduction by implementing the (4Rs) has to be done in order to minimize the amounts of generated waste; therefore reusing products or making them with the least materials will alleviate waste tremendously; hence, less materials to be recycled or sent to landfills. Also, creating sources of revenue in the system is very crucial and this can happen by having a satisfying collection fee via cross subsidy, private sector investment, polluter pays, SWM tax, waste valorization, etc. In addition, having a solid recycling plan and benefitting from the local recycling systems such as Zabbaleen and private sector will be of added value to the waste management chain and will increase system's efficiency. Having capacity building that can develop the waste management system and aid in engineered landfills design will lead to less ecological and minimum public health problems resulting from mismanagement of waste. Additionally, raising awareness on integrated sustainable waste management will change the attitude and behavior towards dealing with waste. Finally, integration among all stakeholders, waste system elements, and all aspects must take place with regular follow-up and monitoring. By doing such efforts in municipal solid waste management, a road will be paved for a better future for the upcoming generations leading to sustainability in waste management.